VD_FINDINFO HC / 2009 / 447 vom 7. Dezember 2009 - VD Tribunal cantonal (2009)
MESURE PROVISIONNELLE, ACTION EN DIVORCE, DIVORCE, VISITE, SURVEILLANCEEN GÉNÉRAL | 133 al. 1 CC, 133 al. 2 CC, 133 CC, 138 CC, 273 CC, 274 CC, 103 CPC, 243 CPC